Influence of Appreciative Intelligence and Innovation Factors on Innovation: An Empirical Study - M. Vishwanath Pai; P. S. Aithal, (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: Innovation is a critical factor for everlasting success of an organization. Innovation factors along with Appreciative Intelligence are the essential characteristics an organization should have to tread upon the path of successful innovation. Every organization follows some processes, protocols and practices for the day to day and long term operations. Some practices form an important aspect for the success of an organization. Certain practices followed become critical characteristics to beat the competition. Bench marking is always very important to know the strength and weakness of an organization. Thus every organization should know their potential in innovation curve. Since the components of Innovation factors and Appreciative Intelligence are both tangible and intangible, measuring the influence of each of them is not linear. A specific tool developed by me is used for this purpose. The result is analysed to reveal the innovation capability of an organization. Depending on the result measures can be taken by the organization to enhance their innovation potential. Design/Methodology/Approach: Companies belonging to different sectors are contacted and the online tool is circulated among the employees to give the details. The details given are analysed with another tool. Findings/Result: Based on the data received from the tool developed which has components of both Innovation Factors and Appreciative Intelligence the Innovation capability of the organization is inferred. It is found out that an organization which has imbibed the characteristics of Innovation factors and Appreciative Intelligence are more Innovative and successful. Originality/Value: The tool developed can be used to benchmark an organization on their Innovation Capability and to improve if need be. Paper Type: Empirical Research